Maternalism and new imperialism in Russia: “good mothers” for a militarizing state—expectations, implications, and resistances - Gradskova, Yulia (Frontiers in Sociology, 2023)
This article explores maternalism in Russia in the context of the contemporary Russian authoritarian state. In particular, I analyze what implications maternalism has for women, mothers, and families on the one hand and how it is connected to the Russian state's new imperial ambitions on the other. I also explore how maternalism is challenged and employed by those resisting state politics, including militarism. Historically, maternalism was used for the analysis of the development of the welfare state in Europe and beyond and for studying women's activism that contributed to significant changes in the state's welfare politics. Maternalism in European history could be seen as “a progressive heterosexual maternal womanhood”; according to Mary Daly, it could be explained as a recognition of the “existence of a uniquely feminine value system based on care and nurturing” and as the assumption that women are performing “a service to the state by raising citizen-workers”. Gender historians of Latin America showed that speaking from the position of a mother was quite important for claiming both the right to be accepted as an equal citizen and the improvement of maternity care, welfare, and living conditions for mothers and children. Furthermore, maternalism was widely used in protests against state militarism, wars, and military dictatorships, not least as a part of the campaign against the Vietnam War or the crimes of the Argentinian military dictatorship. However, maternalism was also widely used by several totalitarian regimes, including fascism and Stalinism. Maternalism was an important political instrument used by the state socialist discourse in order to show the superiority of the “socialist” welfare system over the “capitalist” one and to make this system appear attractive to women from “developing” countries.